INTRACARDIAC AND PERIPHERAL CIRCULATING ENDOTHELIAL MICROPARTICLES ARE ASSOCIATED WITH CENTRAL SYSTOLIC BLOOD PRESSURE IN PATIENTS WITH CORONARY ARTERY DISEASE. (June 2018) - Gkaliagkousi, E.; Gavriilaki, E.; Vasileiadis, I.; Yannaki, E.; Mavrogianni, A.; Tsiakmakopoulos, K.; Nikolaidou, B.; Anyfanti, P.; Markala, D.; Zarifis, I.; Douma, S.
Abstract : Objective: Circulating endothelial microparticles (EMPs) are expected to reflect underlying endothelial damage observed in coronary artery disease (CAD). However, it is not clear if and in what extent, EMPs increase in acute coronary syndromes (ACS) compared to stable CAD and whether they reflect local or systemic cardiovascular damage. Design and method: We enrolled consecutive adult patients with a clinical indication for coronary angiography in our Cardiology Department during a 1-year period. Central blood pressure (cBP) measured during angiography and patients' history were recorded. Coronary sinus and peripheral blood samples were collected. Flow cytometry protocol was standardized based on previous studies. Double-positive events for Annexin and CD144 in the microparticles region were measured and quantified using Flow Count Fluorospheres. Results: We have studied 38 patients with ACS (22 STEMI and 16 NSTEMI), 17 patients with stable CAD and 6 control patients (Table 1). We found significantly increased EMPs in patients with CAD compared to controls, both in peripheral (p = 0.001) and coronary circulation (p = 0.003). This confirmed the validity of our method and the absence of artificial or ex vivo activation. Then, we analyzed EMPs in ACS versus stable CAD. ACS patients had significantly increased EMPs both in peripheral (p = 0.008) and coronary circulation (p = 0.045), compared to stable CAD (Figure 1). No difference was found in patients with STEMI versus NSTEMI. Furthermore, coronary EMPs were significantly increased compared to peripheral (p = 0.021). Although no association was found with traditional cardiovascular risk factors, both peripheral (r = 0.489, p = 0.003) and coronary (r = 0.312, p = 0.048) EMPs were associated with cSBP. Figure. No caption available. Conclusions: EMPs are increased in patients with ACS versus stable CAD and exhibit a profound increase in the coronary circulation compared to periphery, indicative of ongoing endothelial damage during acute myocardial ischemia. The extent of this damage may have implications regarding treatment and prognosis in these patients. The association between EMPs and cSBP possibly reflects an effect of endothelial dysfunction on central hemodynamics and aortic stiffness. Further prospective studies are needed to better clarify the role of microparticles as prognostic and possibly therapeutic targets.